Teaching Parents via Online Asynchronous Training to Use Speech-Generating Devices with Their Autistic Children: A Pilot Study - Lauren Fischbacher; Robin L. Dodds; Ingrid Shiyin Tien (MDPI AG, 2024)
Background/Objectives: Telepractice interventions have been found to alleviate barriers families face when seeking communication interventions. This study is a multiple-baseline single-subject design that measures parent communication opportunities and parent responsiveness to determine if parent training through online modules created for parents of children with communication support needs can be effective for training parents of autistic children with communication support needs. Methods: This study replicates work by utilizing online training used as well as the same variables and definitions. This study expands the original study by providing the children with speech-generating devices (SGDs). SGDs are an assistive technology tool to increase language production and give access to language to minimally verbal autistic people. A central difference between this study and study is that the only training parents received was the online modules and written instructions to set up the SGD. Results: Overall, the POWR modules appear to positively impact the communication opportunities provided by the parent during play and activities, increase child communication, and improve parent proficiency in implementing the POWR strategy. Conclusions: There is a need for a larger single-case study or a randomized control trial to replicate these findings. Additional instruction may be needed for parents of children with autism around responsive interactions. This study adds to innovative ways of providing family-centered training and access to AAC for those with barriers to service.